Compressional deformation along the Chañarcillo basin west margin: North Chilean Late Jurassic-Early Cretaceous back-arc basin - Amilibia, A. (TRABAJOS DE GEOLOGÍA, 2009)
The study area is located at the boundary between the Central Andes Coastal Cordillera and Precordillera morphostructural units (CCPB) that corresponds to the west margin of the mainly volcanic, subduction related, Late Jurassic-Early Cretaceous back-arc basin of northern Chile. Around Copiapó, this margin describes an E-verging NNE-SSW-trending regional scale anticline, result of the basin inversion under transpressional regime at Albian times. The anticline involves volcanic Punta del Cobre formation and marine Chañarcillo group syn-extensional sequences. Overlying Cerrillos formation conglomerates, deposited synchronously to the basin inversion, has been interpreted as the distal part of a fan-delta system located at the western border of the basin.